Incorporation of Extracted Mucor indicus Fungus Chitin Nanofibers into Starch Biopolymer: Morphological, Physical, and Mechanical Evaluation. (23rd April 2021) - Bahrami, Bahador; Behzad, Tayebeh; Salehinik, Fatemeh; Zamani, Akram; Heidarian, Pejman
Abstract: Bio‐nanocomposites based on starch are reinforced by different percentages of chitin nanofibers (ChNFs) and compatibilized by glycerol. Nanofibers are extracted from Mucor indicus fungus through different chemo‐mechanical pretreatments. The mechnical, chemo‐physical, and morphological properties of the nanocomposite starch films were evaluated and compared with the unfilled thermoplastic starch (TPS) film. Based on the obtained results, Young's modulus of the film at 5 wt.% ChNFs indicated 239% enhancement compared to the TPS film due to the existence of good interactions between starch and ChNFs. Moreover, the ultimate strength of the reinforced film at 5 wt.% ChNFs and the unreinforced counterpart are found to be 5.5 and 1.74 MPa, indicating 216% improvement; however, the elongation at break of the films decreases from 59.3% to 19.3% by adding 5 wt.% ChNFs. In addition, the moisture absorption of the film decreases after the incorporation of ChNFs. Based on the morphological study, ChNFs increase the roughness of the starch matrix with a homogenous morphology revealing the good dispersion of nanofibers in the TPS film. Finally, the nanocomposite film with 5 wt.% ChNFs show the best properties to employ for bio‐film applications. Abstract : There is no study using the fungal based chitin nanofibers (ChNFs) for production of starch based nanocomposites. The novelty of current study is to isolate ChNFs from Mucor indicus fungus in optimal medium cultivation by chemo‐mechanical pretreatments. The Young's modulus and ultimate strength of the film at 5 wt.% ChNFs indicate 239% and 216% improvement, respectively. ​